Retinal changes in generalized anxiety disorder patients - Baykara, Sema; Kazgan, Asli; Yildirim, Hakan; Tabara, Muhammed Fatih; Kasikci, Halim Omer; Keles, Denizhan Danaci (Sage Publications Inc, 2024)
Objective: Optical coherence tomography (OCT) is a method that allows high-resolution cross-sectional imaging of biological tissues. It was suggested that changes in the cranial structure or functions would be reflected in the retina. OCT has been an important method in the diagnosis and follow-up of diseases via morphometric or quantitative retinal measurements. Free radicals, inflammatory processes, and neurotransmission disorders play a role in the etiology of generalized anxiety disorder (GAD). The study aimed to demonstrate the retinal changes in GAD patients due to neurodegeneration based on the comparison of the OCT data of the GAD patients and controls, and the differences between OCT findings of GAD patients and those of controls. Methods: The study group included 21 GAD patients. The control group included 21 individuals without any known psychiatric or organic disease, including eye diseases. Results: There was a statistically significant difference between the macular volumes (MV) of the GAD and control groups, the macular volume was lower in the GAD group. There were positive correlations between BDI scores and MV, GCLT, RNFLT-i, RNFLT-n, between BAE scores and (RNFLT-n), and between the CGI severity scale scores and MV, RNFLT-n, and RNFLT-t. Conclusion: OCT analysis of the GAD patients demonstrated that MV values were lower when compared to the control group. Patients with GAD should be screened for these retinal changes. OCT, a simple, non-invasive, and relatively inexpensive method could be employed as a supplementary method in the follow-up of GAD patients.
Keywords: anxiety disorders; tomography; optical coherence; retina; nerve fibers